Magnetic properties of the Mg2FeV3O11-x site-disordered vanadate - Guskos, N.; V. Likodimos; Typek, J.; Zolnierkiewicz, G.; Szymczak, R.; Blonska-Tabero, A. (Journal of Non-Crystalline Solids, 2006)
The magnetic properties of the Mg2FeV3O11-x ternary vanadate, characterized by disorder between diamagnetic Mg2+ and high-spin Fe3+ ions, are studied using dc magnetization and electron paramagnetic resonance (EPR). The dc susceptibility shows antiferromagnetic interactions between Fe3+ spins with a Curie-Weiss temperature of Θ = -50(1) K, followed by spin-glass-like freezing at Tf ≈ 2.8 K, suggesting significant spin frustration. Temperature-dependent EPR measurements confirm the antiferromagnetic coupling of Fe3+ spins at high temperatures, while a distinct divergence is observed at T ≈ 50 K. This behavior is associated with the formation of spin clusters providing two different energy scales for the magnetic interactions. The magnetic response of Mg2FeV3O11-x is similar to that of the Zn-analogue compound, though the observed differences of the implicated energy scales indicate that magnetic inhomogeneity depends on the extent of cation disorder.